PERANCANGAN MEDIA PEMBELAJARAN INTERAKTIF VIDEO BELARA PADA MATERI BERNYANYI LAGU DAERAH SEKOLAH DASAR - Ilma Siti Salamah; Prihantini; Uus Kusnadi; Kuswanto, Kuswanto (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Indonesia is a country that has a diversity of different cultures and regional songs. However, students have difficulty singing regional songs because they do not understand singing techniques, the language of the lyrics is too difficult for students to sing because there is no supporting media in learning to sing so regional songs are less popular with students. Technology-based media can be used as a means of implementing learning. The aim of this research is to develop BELARA video media to make it easier for students to sing regional songs. The research method applies Design and Development (D&D) with the ADDIE model which includes 5 stages, namely, Analyze, Design, Development, Implementation, Evaluation. Media design is carried out starting from designing storyboards, designing and editing BELARA videos. The media developed includes the songs Tokecang and Cing Cangkeling which originate from West Java. With the interactive video media BELARA, it can facilitate and increase students' interest in singing regional songs.